Development of tourism in Huila: Current situation 2021 and future challenges - Mora, Natalia
Tourism is open mentioned as one of the main engines of economic development in the department of Huila. This as a result of a new conception of the globalized world, ease of access to information, better income and greater availability of time that people spend to travel and discover new designations. In this sense and given the importance of tourism for the regional economy, it is necessary to know first-hand the current state of tourism after the pandemic, as well as analyze the trends of the national and international tourism market in order to obtain significant information, complete and timely for the highly changing and complex regional tourism environment, which will be of great consideration when making assertive decisions that allow reactivating and stimulating the improvement and/or growth of this economic sector in the department.